2017
DOI: 10.18393/ejss.286550
|View full text |Cite
|
Sign up to set email alerts
|

Response of fodder sorghum (Sorghum bicolor (L.) to sewage sludge treatment and irrigation intervals in a dryland condition

Abstract: Article Info Received : 08.08.2016 Accepted : 07.11.2016 A field experiment was conducted in the Experimental Research Farm of Omdurman Islamic University, Sudan to determine short-term effect of irrigation intervals (7 and 10 days) and sun-dried or composted sewage sludge, recommended mineral fertilizer on straw dry matter yield (SDMY) and N, P and K content of fodder sorghum and soil properties. In the 7 and 10 days irrigation intervals, composted, sun-dried sludge and mineral fertilizer have significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…This was earlier supported that the sensitivity of water retention to changes in organic matter content was highest in sandy soils (Rawls et al 2003). Under similar conditions to our study, successive application of composts improved soil physical properties (Agbede et al 2008) and increased water retention capacity due to increased pore volumes and reduced bulk density (Shashoug et al 2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was earlier supported that the sensitivity of water retention to changes in organic matter content was highest in sandy soils (Rawls et al 2003). Under similar conditions to our study, successive application of composts improved soil physical properties (Agbede et al 2008) and increased water retention capacity due to increased pore volumes and reduced bulk density (Shashoug et al 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Under the prevailing environmental conditions of our study, Elkerim (2012) found that higher grain yield and yield components of sorghum with application of 15 t ha -1 of compost from farm yard manure. Application of compost in an irrigated sandy loam soils with increased irrigation cycle resulted in similar sorghum yield to recommended irrigation cycle (Shashoug et al 2017). Similarly, due to higher quantity of macro and micronutrients added to the soil in the form of farm yard manure, an increase of 24% in grain yield of millet was reported (Ullasa et al 2017).…”
Section: Discussionmentioning
confidence: 92%
“…With increasing energy consumption from renewable sources, sewage sludge (SS) is increasingly seen as a promising fertilizer for energy crops [1][2][3]. Due to the fact that sewage sludge contains large amounts of organic and inorganic nutrients, it can complement or replace chemical fertilizers [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…SS is a by product of waste water treatment process, which contains lots of organic matter, plant nutrients (N, P, K, Ca, Mg, etc) and harmful components such as potential toxic heavy metals and pathogenic microorganisms (Delibacak et al, 2020;Kızılkaya et al, 2021). The use of SS in agriculture includes several operations that improve its efficiency in crop production, as compared to mineral fertilizers, which are related to the stabilising process before spreading (Shashoug et al, 2017;Jatav et al, 2021). These are principally aerobic digestion, anaerobic digestion, composting, liming, and pelletisation.…”
Section: Introductionmentioning
confidence: 99%